Modeling economic growth in contemporary Greece - Vlachos, Vasileios,; Bitzenis, Aristidis,; Sergi, Bruno S., (Entrepreneurship and global economic growth.)
In the aftermath of the devastating economic depression suffered for almost a decade, Modeling Economic Growth in Contemporary Greece assesses the conditions shaping the Greek economy's restart, discussing the effect of institutions on the business environment and highlighting the factors which are critical for achieving sustainable economic growth. The intrinsic properties of the Greek economic and business environment imply that there are country-specific factors responsible for the performance of the Greek economy, which is differentiated from its European counterparts. Despite being a member of the European Union since 1981 and one of the twelve first countries who adopted the euro, Greece has not been able to converge in crucial macroeconomic indicators with the early euro area Member States. The European stimulus package to support post COVID-19 recovery appears as a unique opportunity for Greece to develop a long-term vision and materialize reforms that will unlock the economy's true potential. This latest book in the Entrepreneurship and Global Economic Growth series is centred around the determinants of and obstacles to Greece's sustainable economic growth, presenting the macroeconomic and external environment and the dynamics of Greek economy and focuses onto internal conditions shaped by country-specific characteristics affecting labor and product markets' efficiency and the performance of institutions and production factors.